Access time and complications in central venous catheter insertion in patients presenting to the emergency department of a tertiary hospital: A prospective cohort - Fareed Ahmed; Umaira Aftab; Salman Muhammad Soomar; Asher Feroz; Zeyanna Dhalla; Emaduddin Siddiqui (Taylor & Francis Group, 2023)
AbstractObjective: This study compares the access time and procedural-related complications in CVC insertion via ultrasound guidance versus the landmark technique. Methods: A prospective cohort study was performed in the emergency department of a tertiary care hospital from January 2016 to December 2018. Patients with the indication of CVC insertion were included. Primary outcomes included access time and total procedure time; secondary outcomes included post-procedural complications. Seldinger's Technique was adopted for CVC insertion in both groups. For qualitative variables, chi-squared and Fisher's exact tests were applied, and quantitative variables were reported as mean and standard deviation. Differences were assessed by the independent t-test and the Mann-Whitney test. Results: A total of 252 patients were enrolled and divided into exposed (ultrasound-guided technique) and unexposed (landmark guided technique) groups. Insertion of CVC on the first attempt was successful in 82 patients (62.1%) in the ultrasound group and in 68 patients (56.7%) in the landmark group. The mean access time (seconds) in the exposed group was 21.9 and in the unexposed group was 29.9 with a mean difference of only 8 seconds. The total procedural time (in minutes) was 32.2 versus 22.7 sequentially with a mean difference of 9.5 minutes. Fewer venipuncture attempts and arterial pricks were recorded in the exposed group (1.4 and 10/132) as compared to the unexposed group (1.8 and 36/120). Conclusion: Ultrasonographical-inserted CVC had a higher success rate with fewer post-procedural complications but required longer total procedural time with inappreciable access time.